1995
DOI: 10.1002/bjs.1800820604
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and vascular disease

Abstract: There is increasing evidence that a raised blood level of homocysteine (HC) is a risk factor for premature atherosclerosis. With a gene frequency between one in 70 and one in 200 this condition may be more common than previously thought. It should be suspected especially in young patients in whom other risk factors are absent. The diagnosis may be made by demonstrating raised plasma HC levels, either basally or after methionine loading. Studies have shown significantly increased levels of HC in patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…They calculated the odds ratio of a 5 mol/L increment of plasma HCy level for coronary artery disease of 1.6, cerebrovascular disease of 1.5, and for peripheral vascular disease of 6.8. These results have been supported by a further 40 subsequent studies [3]. Thirty percent of patients presenting to vascular clinics-the figure may be nearer 50% to 60% in patients undergoing vascular intervention [4]-have elevated plasma HCy, compared with 2% to 5% in the normal population [5].…”
Section: Introductionsupporting
confidence: 56%
“…They calculated the odds ratio of a 5 mol/L increment of plasma HCy level for coronary artery disease of 1.6, cerebrovascular disease of 1.5, and for peripheral vascular disease of 6.8. These results have been supported by a further 40 subsequent studies [3]. Thirty percent of patients presenting to vascular clinics-the figure may be nearer 50% to 60% in patients undergoing vascular intervention [4]-have elevated plasma HCy, compared with 2% to 5% in the normal population [5].…”
Section: Introductionsupporting
confidence: 56%
“…Normal plasma levels of HC are in the range of 1 ± 10 mM (Berwanger et al, 1995) but in homocysteinaemic patients plasma HC levels of 100 ± 500 mM have been detected (Malinow, 1994). In the present study, addition of HC alone, at a concentration of 100 mM, had no signi®cant eect on endothelium-dependent relaxation.…”
Section: Discussionmentioning
confidence: 42%
“…Elevated plasma levels of the sulphur-containing amino acid homocysteine (HC) are suggested to be a powerful independent risk factor for premature atherosclerosis and other in¯ammatory vascular diseases (Berwanger et al, 1995;McCully, 1996). Vascular endothelial cell dysfunction is considered to be a major factor in the development of atherosclerosis (Ross, 1993), and recent studies have shown that mild to moderate elevations in plasma levels of HC (20 ± 35 mM) are associated with impaired endothelium-dependent arterial dilatation in both humans (Tawakol et al, 1997;Woo et al, 1997) and monkeys (Lentz et al, 1996) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that PCOS is associated with cardiovascular disease risk factors such as obesity, insulin resistance, type 2 diabetes, elevated blood pressures and dyslipidemia. However, all of these abnormalities are also common in obese subjects [17,18].…”
Section: Discussionmentioning
confidence: 94%